(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the word stress and its definitions, their characteristics, similarities and differences are analyzed in detail. The importance of word stress in the language is analyzed mainly on the example of English and Uzbek languages, and different views are expressed. How the accent is connected with syllable structures, how it is reflected in the speech and how it is realized will be explained from a theoretical point of view. Factors in the formation of word stress are studied in a comparative method based on the views of Russian, English, and Uzbek scholars, and the differences between these views are shown. It is proved by examples that sentence and word stress are interrelated phenomena.